A bovine miRNA, bta‐miR‐154c, withstands in vitro human digestion but does not affect cell viability of colorectal human cell lines after transfection - Pieri, Myrtani; Theori, Elena; Dweep, Harsh; Flourentzou, Myrofora; Kalampalika, Foteini; Maniori, Maria‐Arsenia; Papagregoriou, Gregory; Papaneophytou, Christos; Felekkis, Kyriacos (FEBS open bio, 2022)
Colorectal cancer (CRC) is the third most frequent human cancer with over 1.3 million new cases globally. CRC is a complex disease caused by interactions between genetic and environmental factors; in particular, high consumption of red meat, including beef, is considered a risk factor for CRC initiation and progression. Recent data demonstrate that exogenous microRNAs (miRNAs) entering the body via ingestion could pose an effect on the consumer. In this study, we focused on bovine miRNAs that do not share a seed sequence with humans and mice. We identified bta‐miR‐154c, a bovine miRNA found in edible parts of beef and predicted via cross‐species bioinformatic analysis to affect cancer‐related pathways in human cells. When bovine tissue was subjected to cooking and a simulation of human digestion, bta‐miR‐154c was still detected after all procedures, albeit at reduced concentrations. However, lipofection of bta‐miR‐154c in three different colorectal human cell lines did not affect their viability as evaluated at various time points and concentrations. These data indicate that bta‐miR‐154c (a) may affect cancer‐related pathways in human cells, (b) can withstand digestion and be detected after all stages of an in vitro digestion protocol, but (c) it does not appear to alter epithelial cell viability after entering human enterocytes, even at supraphysiological amounts. Further experiments will elucidate whether bta‐miR‐154c exerts a different functional effect on the human gut epithelium, which may cause it to contribute to CRC progression through its consumption. MicroRNAs (miRNAs) are small RNA molecules present in foodstuffs. Here, we show that bovine miRNA, bta‐miR‐154c, is predicted to affect cancer‐related pathways in humans and can withstand a model of human digestion. However, it does not affect cell viability after uptake by epithelial cancer cells. Future studies will determine whether ingested miRNAs affect human enterocytes, thereby contributing to the progression of colorectal cancer.